Avicenna on Melancholy and its Treatment: A Philosophical Approach - Mahmud Saidi; Hossein Zamaniha (حکمت سینوی)
The question of the relationship between the rational soul and the body, and the mediating role of the vaporous soul, has led to the formation of many philosophical discussions in this area. One of these cases is the causes and symptoms of mental illnesses, such as melancholic depression, which, from Avicenna's perspective, the most important reason for its occurrence and the most effective method of treatment should be sought in the relationship between the rational soul and the body. Melancholic depression means the deviation of human thoughts and mental images from the correct path, in which case the correspondence of cognitive concepts with the external world is disrupted, and therefore the person is immersed in their own incorrect thoughts and beliefs. This mental illness has different levels, and in its most severe form, mania, the patient's perceptions are greatly deviated from the real world, they constantly think about the dead, and may consider themselves dead. From Avicenna's point of view, the main cause of this disease should be sought in the weakness of the vaporous soul, which weakens the connection between the soul and the body. The root of this weakness is also the predominance of the melancholic temperament in the brain, which disrupts the function of the vaporous soul as the link between the soul and the body. Overall, Avicenna's approach to melancholic depression shows his comprehensive approach to mental disorders, an approach that is rooted both in his philosophical foundations and in empirical evidence and studies.